SOLUSI MENGATASI DUALITAS PENGATURAN SANKSI ADMINISTRASI ATAU SANKSI PIDANA DALAM UNDANG-UNDANG KETENTUAN UMUM PERPAJAKAN - Suharsono, Agus; Prasetyoningsih, Nanik (Jurnal Yuridis, 2023)
This study analyzes the duality of the provisions for imposing administrative sanctions or criminal sanctions for taxpayers who do not register themselves to be given an Taxpayer Identification Numbers or do not report their business to be confirmed as Taxable Persons for VAT Purposes, causing state losses because it can lead to legal uncertainty and injustice. This paper is a doctrinal research that analyzes primary and secondary sources of law with statutory, conceptual, and analytical approaches. The results of the research show that the Law on General Provisions and Procedures for Taxation already regulates administrative sanctions for taxpayers who do not register themselves to be given a Taxpayer Identification Number or do not report their business to be confirmed as a Taxable Persons for VAT Purposes, causing state losses, namely by granting a Taxpayer Identification Number and inauguration of a Taxable Persons for VAT Purposes as a position and issuing Notice of Tax Underpayment Assessment along with administrative sanctions. Based on the principles of establishing laws and regulations and the legal principles of hulprecht, una via, ultimum remedium, and nullum delictum, nulla poena, sine praevia lege poenali, because there are provisions for the imposition of administrative sanctions, for legal certainty and justice the provisions of Article 39 paragraph (1) letter a of the General Provisions and Tax Procedures Act should be abolished so that there is no duality in the imposition of sanctions for the same violation.